Board Indicators, Managerial Ownership, Intellectual Capital and Earnings Quality in Consumer Goods of Indonesia and Malaysia - Saarce Elsye Hatane; Natalia Ivana Halim; Josua Tarigan (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2019)
This paper studies the influence of the board of director with earnings quality, using intellectual capital as a mediating variable. Also, it takes account of concomitant variables such as firm size and leverage. The subject of the study focuses on companies in the consumer goods sector listed in the stock exchange of Indonesia and Malaysia is 2011-201. Board of director (BOD) is found to have a negative impact on earnings quality (EQ) in Indonesia, whereas it has no impact on earnings quality in Malaysia companies. On contrary, the board of director has a positive influence on intellectual capital (IC) in Indonesia. The opposite influence has been found in Malaysia where BOD is negatively correlated to IC. IC has a significant influence towards EQ in both countries. IC has a positive impact on EQ in Indonesia, but the effect is found to be negative in Malaysian firms. In both cases, IC has failed to become a mediation variable towards the impact of BOD to EQ. Therefore, the optimization of BOD is crucial in enhancing EQ in Indonesia. At the same time, IC has prominence in influencing EQ in Indonesia and Malaysia thus raising the importance of its optimization.